2001
DOI: 10.1515/mgmc.2001.24.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Formation of the First Doubly Benzylic 1,1-Di-Grignard Reagent

Abstract: Reaction of l-bromo-2-(l-chloro-l-trimethylsilylmethyl)benzene (3) with magnesium in THF expectedly gave the corresponding 1,3-di-Grignard reagent lb in 44 % yield, but in addition, the isomeric 1,1-di-Grignard reagent 4 was obtained in equal amounts. Compound 4 is remarkable for two reasons: it is one of the few examples of a 1,1-di-Grignard reagent, and its formation involves rearrangement by 1,3-migration of a trimethylsilyl group which provides further evidence for the occurrence of carbanionic intermediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Therefore, one may conclude the reaction of 1b with magnesium leads not only to the unrearranged Grignard reagent 2b but also to the rearranged 3b (Scheme ); this process occurs only during the formation reaction and not afterward, and this again is ascribed to the highly reactive carbanionic intermediate 9b analogous to 9a (Scheme ). We recently reported that in the related case of the formation of di-Grignard reagents from 54 , only intramolecular migration of the trimethylsilyl group occurred, leading to a mixture of 55 and 56 14 …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, one may conclude the reaction of 1b with magnesium leads not only to the unrearranged Grignard reagent 2b but also to the rearranged 3b (Scheme ); this process occurs only during the formation reaction and not afterward, and this again is ascribed to the highly reactive carbanionic intermediate 9b analogous to 9a (Scheme ). We recently reported that in the related case of the formation of di-Grignard reagents from 54 , only intramolecular migration of the trimethylsilyl group occurred, leading to a mixture of 55 and 56 14 …”
Section: Resultsmentioning
confidence: 99%
“…Presumably, it has an oligomeric or polymeric structure, as it is rather poorly soluble; even in THF, which normally is a powerful solvent for organomagnesium compounds, the solubility is only about 0.0016 M. On one hand, this property is convenient if one wishes to obtain pure la, because on preparation from the corresponding dihalide 2a and magnesium, the primarily formed di-Grignard reagent 3a undergoes the Schlenck equilibrium with la from which the latter precipitates in pure form. While the formation of 3b' was of considerable mechanistic interest as it proceeds via a carbanionic intermediate [10], 3b could not be obtained pure, and hence the corresponding diorganylmagnesium lb was not accessible by this route. A conceivable strategy to enhance the solubility is the introduction of bulkier groups which might act not only by increasing the lipophilicity of the reagent, but also by counteracting association.…”
Section: Introductionmentioning
confidence: 99%